Advance technique for online condition monitoring of surge arresters - Khopkar, Anil S.; Pandya, Kartik S. (Institute of Advanced Engineering and Science, 2025)
Gapless surge arresters (GLSA) constructed with zinc oxide (ZnO) element is connected in electrical power system for protection against surge voltage. For condition monitoring of GLSA conventionally offline and online techniques are available. However, offline techniques are not much useful as it requires system shutdown and hence online techniques are more useful. Online surge arrester monitoring technique based on leakage current analysis is adopted by all stakeholders. However, in this method supply system harmonics plays major roles in measurement accuracy to determine health index. In this paper improved health monitoring indexes for GLSA diagnostic based on ratios of leakage current components has been proposed. The ageing process has been done with application of lightning Impulse current, surface contamination due to salt fog, temperature effect, and moisture ingress. Various experimental tests have been carried out on porcelain and polymer housed surge arresters to evaluate the ability of proposed method. Obtained results of 9 kV, 18 kV, and 30 kV healthy and degraded metal oxide GLSAs have been shown the viability of improved health indexes on surge arrester condition monitoring procedures. The experimental investigation and discussion of the obtained results reflects sufficient and effective trails to utility engineers to determine health of surge arresters and able to effectively schedule further maintenance plan.